Disclosure of socio-environmental scandals and corporate reputation - William Augusto Sousa de Oliveira; Reiner Alves Botinha (Revista Contabilidade & Finanças)
ABSTRACT This research aimed to investigate the use of neutralization of disclosure of socio-environmental scandals and its relationship with corporate reputation. No studies were found observing the strategies and motivations of socio-environmental disclosure from a theoretical lens like the literature on neutralization techniques. This study sought its relevance by investigating the disclosure and reputation maintenance strategies used by companies involved in national socio-environmental scandals, identifying various paths for information neutralization, guided by the origin of each case and business motivations, in addition to highlighting empirical findings that stimulate the advance in research on neutralization techniques in corporate reports. The aim is to assist students and researchers by providing new evidence for corporate processes that involve socio-environmental disclosure strategies and reputational management. As well as contribute to ensuring that stakeholders see voluntary socio-environmental information better and in a well-founded manner, seeking to qualify decision-making. Corporations involved in the main national socio-environmental scandals between 2014 and 2021 were analyzed. This is an exploratory and quali-quantitative study, with content analysis and statistical tests to investigate socio-environmental scandals. Neutralization techniques were identified in information from voluntary corporate reports by companies involved in socio-environmental scandals. In addition to finding a positive correlation between neutralized disclosure and the reputation of these companies in the year the scandal took place and in the year after, there was also an increased use of techniques after the event. We hope to contribute to the literature by proposing the insertion of neutralization techniques in the investigation of strategies involving voluntary disclosure and corporate reputation. With a practical approach, we seek to build a rather critical view regarding voluntary reports and business mechanisms that may disqualify the information contained in them.